1989
DOI: 10.1016/0014-5793(89)81129-9
|View full text |Cite
|
Sign up to set email alerts
|

The light chain but not the heavy chain of botulinum A toxin inhibits exocytosis from permeabilized adrenal chromaffin cells

Abstract: The heavy and light chains of ~t~~~ A toxin were separated by anion exchange c~o~to~aphy. Their intracelltiar actions were studied using bovine adrenal chromafhn cells penneabilimd with streptolysin 0. Purified light chain inhibited the Gas +-stimulated p~o~~~ne release with a l&f-maximal effect at about 1.8 nM. The inhibition was incomplete. Heavy chain up to 28 nM was neither effective by itself nor did it enhance the inhibitory effect of light chain. It is concluded that the light chain of botulinum A toxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

1990
1990
1999
1999

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(29 citation statements)
references
References 21 publications
1
26
1
1
Order By: Relevance
“…Ahnert-Hilger et al [6] have shown inhibition of catecholamine release from permeabilised adrenal chromaffin cells after treatment with the light chain of tetanus toxin alone or with the two-chain form in the presence of a reducing agent. Similar activities of the light chains of tetanus and of botulinum toxins (which are thought to have similar molecular mechanisms) have also been reported in other systems [7,8]. On the other hand, Poulain et al [9], working on Apiysia, reported that both the light and the heavy chains of botulinum toxin need to enter the cell before an effect is observed.…”
Section: Introduction Tetanus Toxin Is a Neurotoxin Secreted Bysupporting
confidence: 52%
“…Ahnert-Hilger et al [6] have shown inhibition of catecholamine release from permeabilised adrenal chromaffin cells after treatment with the light chain of tetanus toxin alone or with the two-chain form in the presence of a reducing agent. Similar activities of the light chains of tetanus and of botulinum toxins (which are thought to have similar molecular mechanisms) have also been reported in other systems [7,8]. On the other hand, Poulain et al [9], working on Apiysia, reported that both the light and the heavy chains of botulinum toxin need to enter the cell before an effect is observed.…”
Section: Introduction Tetanus Toxin Is a Neurotoxin Secreted Bysupporting
confidence: 52%
“…Again the situation resembles the one seen within chromaffin cells. Here the heavy chain does not change or rat her reduces the potency of the light chains of botulinum A toxin 21 or tetanus toxin. ' By contrast, in invertebrate neurons, such as those of the buccal ganglia of Aplysia, the roles of the chains are different.…”
Section: Discussionmentioning
confidence: 99%
“…Catecholamine release from adrenal chromaffin cells, vasopressin release from neurohypophysial terminals and insulin release from pancreatic 13 cells is inhibited by botulinum neurotoxin A [14][15][16][17][18]. However, the variable cleavage of SNAP-25 in pancreatic [3 cells, the incomplete inhibition of vasopressin and catecholamine release and the preferential attack of ATP-dependent priming by botulinum neurotoxin A suggested that this toxin may have molecular targets of different sensitivities [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%